Athlete burnout and the risk of dropout among young elite handball players - Isoard-Gautheur, S.; Guillet-Descas, E.; Gustafsson, H. (The Sport Psychologist, 2015)
The negative feelings that are part of burnout syndrome may prompt athletes to drop out of their sport. The objective of the current study was therefore to examine the influence of athlete burnout profiles on playing status 6 years later. The participants of this study were 458 boys and girls between 14 and 18 years old (M = 15.44; SD = .95) enrolled in elite handball training centers. Cluster analysis on athlete burnout and multinomial logistic regressions on the playing status were conducted. The results suggest that those individuals with a "higher burnout" profile at Time 1 were more likely to have stopped playing handball 6 years later. It therefore seems important to develop strategies to prevent burnout in young athletes enrolled in elite training structures and to promote long-term engagement and well-being in elite sporting activity.